Ozone activation catalyst as well as preparation method and application thereof

By preparing an ozone-activating catalyst with a cobalt-iron alloy or nickel-iron alloy core and a carbon material shell, the problem of insufficient stability and activity of existing catalysts in complex aquatic environments was solved, achieving efficient and low-cost industrial wastewater treatment.

CN119303579APending Publication Date: 2025-01-14INST OF ADVANCED TECH UNIV OF SCI & TECH OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411425449.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing ozone-activated catalysts lack stability and activity in complex aquatic environments, resulting in low catalytic efficiency and difficulty in effectively treating industrial wastewater.

Method used

A catalyst structure with a cobalt-iron alloy or nickel-iron alloy as the core and carbon material as the shell is prepared by mixing potassium ferricyanide solution with metal ions and surfactants, allowing it to stand, separating it, and then calcining it in a protective atmosphere to form a catalyst in which carbon material encapsulates the metal alloy.

Benefits of technology

This improved the catalytic activity and stability of the catalyst, reduced production costs, facilitated industrial application, and enabled the efficient degradation of pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303579A_ABST
    Figure CN119303579A_ABST
Patent Text Reader

Abstract

The invention provides an ozone activation catalyst and a preparation method and application thereof, and belongs to the technical field of catalytic materials and the technical field of water treatment. The ozone activation catalyst includes: an inner core including a cobalt-iron alloy or a nickel-iron alloy; the shell layer is formed on the outer surface of the inner core, and the shell layer comprises a carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of catalytic materials and the technical field of water treatment, and in particular to an ozone activation catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrialization, the discharge of industrial wastewater is increasing, causing serious damage to the water environment and threatening human health and the balance of the ecosystem. Industrial wastewater has the characteristics of complex composition, high concentration and high toxicity. Its effective treatment has always been the focus and difficulty in the field of water treatment. Advanced Oxidation Processes (AOPs) can efficiently oxidize and remove a variety of difficult-to-degrade and highly toxic organic matter by producing highly oxidative free radicals (ROS), and therefore is regarded as an effective means to solve the problem of industrial wastewater treatment.

[0003] Ozone-based AOPs can effectively remove pollutants without causing secondary pollution, and are widely used in actual industrial wastewater treatment processes. In particular, heterogeneous catalytic ozonation (HCO) technology can effectively improve ozone utilization and pollutant oxidation efficiency, and the reuse of catalysts greatly reduces costs. Among them, efficient and stable heterogeneous ozone catalysts are the core of HCO technology. However, how to prepare highly active catalysts that can remain stable in complex water environments remains a difficulty. Summary of the invention

[0004] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present disclosure provides an ozone activation catalyst and a preparation method and application thereof.

[0005] According to an embodiment of one aspect of the present disclosure, an ozone activation catalyst is provided, comprising: a core comprising a cobalt-iron alloy or a nickel-iron alloy; and a shell formed on the outer surface of the core, wherein the shell comprises a carbon material.

[0006] According to an embodiment of another aspect of the present disclosure, a method for preparing an ozone-activated catalyst is provided, comprising the following steps: slowly adding a potassium ferrocyanide solution to a mixed solution containing metal ions and a surfactant for reaction, and then sequentially allowing the mixture to stand and separate to obtain a precursor; calcining the precursor in a protective atmosphere to obtain the ozone-activated catalyst; wherein the metal ions include cobalt ions or nickel ions.

[0007] According to an embodiment of another aspect of the present disclosure, there is provided an application of the above ozone-activated catalyst or the ozone-activated catalyst prepared by the above preparation method in conjunction with ozone in sewage treatment.

[0008] According to the embodiments of the present disclosure, a low-cost cobalt-iron alloy or nickel-iron alloy is used as the core and a carbon material is used as the shell, that is, the metal alloy is wrapped with the carbon material. The high specific surface area and stability of the carbon material and the high reactivity of the metal material can be combined to obtain an ozone activation catalyst with excellent performance, so as to improve the degradation efficiency of pollutants.

[0009] The ozone activation catalyst provided by the embodiments of the present disclosure has high catalytic activity, good stability, and can be reused.

[0010] The preparation method of the ozone activation catalyst provided in the embodiments of the present disclosure is simple, low in cost, has high application value, and is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 shows a transmission electron microscope image of the ozone activated catalyst provided in Example 1;

[0012] Figure 2 shows a transmission electron microscope image of the ozone activated catalyst provided in Example 4;

[0013] Figure 3 shows a transmission electron microscope image of the ozone activated catalyst provided in Example 5;

[0014] Figure 4 Raman images of ozone activated catalysts provided in Examples 1, 4 and 5 are shown;

[0015] Figure 5 A transmission electron microscope image of the ozone activated catalyst provided in Comparative Example 1 is shown;

[0016] Figure 6 shows the X-ray diffraction images of the ozone activated catalysts provided in Examples 1 and 2;

[0017] Figure 7 shows the X-ray diffraction images of the ozone activated catalysts provided in Examples 2 and 3;

[0018] Figure 8 The X-ray diffraction images of the ozone activated catalysts provided in Example 1 and Comparative Example 2 are shown;

[0019] Fig. 9 The degradation curves of oxalic acid degradation catalyzed by ozone activated catalysts provided in Examples 1 and 2 and Comparative Example 1 are shown;

[0020] Fig.10 The degradation curves of oxalic acid degradation catalyzed by ozone activated catalysts provided in Examples 1, 4 and 5 are shown;

[0021] Fig.11The degradation curves of phenol degradation catalyzed by ozone activated catalysts provided in Examples 1 and 4 are shown;

[0022] Fig.12 The degradation curve of oxalic acid degradation catalyzed by the ozone-activated catalyst provided in Example 1 after five cycles of use is shown. DETAILED DESCRIPTION

[0023] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0024] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0025] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0026] In the related technologies, the utilization efficiency of electrons in metals by ozone-activated catalysts is insufficient, and their stability needs to be further improved. Therefore, designing efficient and stable ozone-activated catalysts is the key to improving the pollutant degradation efficiency of HCO technology and reducing the cost of wastewater treatment.

[0027] Transition metals can be used in the preparation and synthesis of catalysts due to their low cost and high activity, especially metal elements and alloys, which have higher activity. However, the rapid passivation of metal elements and alloys in water limits the application of such materials in water treatment and ozone catalysis.

[0028] In the process of realizing the concept of the present disclosure, it was found that carbon materials can be used to wrap metal materials, combining the stability and high specific surface area of ​​carbon materials with the high activity of metal materials to improve the pollutant degradation efficiency of the HCO system.

[0029] According to an embodiment of one aspect of the present disclosure, an ozone activation catalyst is provided, comprising: a core comprising a cobalt-iron alloy or a nickel-iron alloy; and a shell layer formed on an outer surface of the core, the shell layer comprising a carbon material.

[0030] According to the embodiments of the present disclosure, a low-cost cobalt-iron alloy or nickel-iron alloy is used as the core and a carbon material is used as the shell, that is, the metal alloy is wrapped with the carbon material. The high specific surface area and stability of the carbon material and the high reactivity of the metal material can be combined to obtain an ozone activation catalyst with excellent performance, so as to improve the degradation efficiency of pollutants.

[0031] According to an embodiment of the present disclosure, the core includes a cobalt-iron alloy. Using the iron-cobalt alloy as the core can further improve the catalytic activity of the ozone activation catalyst.

[0032] According to an embodiment of the present disclosure, the size of the ozone activation catalyst is 20-50 nm, preferably 30-40 nm. Specifically, the size of the ozone activation catalyst can be 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0033] According to an embodiment of the present disclosure, the thickness of the shell layer is 2-8 nm, preferably 2-6 nm, and more preferably 4-6 nm. Specifically, the thickness of the shell layer can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm or 8 nm.

[0034] According to the embodiments of the present disclosure, the preferred ozone activation catalyst size and shell size can ensure the high reactivity of the cobalt-iron alloy or nickel-iron alloy core and fully exert the stability of the carbon material shell.

[0035] According to an embodiment of the present disclosure, the molar ratio of cobalt to iron in the cobalt-iron alloy is (2-3): (2-3), preferably 2: (2-3). Specifically, the molar ratio of cobalt to iron in the cobalt-iron alloy may be 1:1, 2.5:2, 2:3, 2.5:3 or 3:2.

[0036] According to an embodiment of the present disclosure, the molar ratio of nickel to iron in the nickel-iron alloy is (2-3): (2-3), preferably 2: (2-3). Specifically, the molar ratio of nickel to iron in the nickel-iron alloy may be 1:1, 2.5:2, 2:3, 2.5:3 or 3:2.

[0037] According to the embodiments of the present disclosure, the preferred molar ratio of cobalt to iron or the molar ratio of nickel to iron can fully exert the activity of each metal.

[0038] According to an embodiment of the present disclosure, the carbon material of the shell layer may include a graphene structure. The graphene structure has a high specific surface area and stability, which helps to improve the performance of the ozone activation catalyst.

[0039] According to another embodiment of the present disclosure, there is provided a method for preparing an ozone activation catalyst, comprising the following steps:

[0040] Slowly adding a potassium ferrocyanide solution into a mixed solution containing metal ions and a surfactant to react, and then sequentially standing and separating to obtain a precursor;

[0041] calcining the precursor in a protective atmosphere to obtain an ozone-activated catalyst;

[0042] Wherein, the metal ions include cobalt ions or nickel ions.

[0043] According to an embodiment of the present disclosure, the precursor may include cobalt ferrocyanide or nickel ferrocyanide.

[0044] According to an embodiment of the present disclosure, the protective atmosphere can be one or more of nitrogen, helium, neon, argon, krypton and xenon. The protective atmosphere can isolate the precursor from the air, prevent the precursor from reacting with oxygen, and ensure the formation of the core metal alloy and the shell carbon material.

[0045] The preparation method of the ozone activation catalyst provided in the embodiments of the present disclosure is simple, low in cost, has high application value, and is convenient for industrial production.

[0046] According to an embodiment of the present disclosure, the metal ions include cobalt ions. Preferred metal ions can further improve the catalytic activity of the prepared ozone activation catalyst.

[0047] According to an embodiment of the present disclosure, the surfactant is a polymer surfactant with a weight average molecular weight of 30000 to 50000, preferably 40000 to 50000. Specifically, the weight average molecular weight may be 30000, 35000, 40000, 45000 or 50000.

[0048] According to an embodiment of the present disclosure, the surfactant is preferably one or more of polyvinyl pyrrolidone, polyacrylic acid, and carboxymethyl cellulose.

[0049] According to the embodiments of the present disclosure, the preferred surfactant is beneficial to ensure the morphology of the ozone activation catalyst.

[0050] According to an embodiment of the present disclosure, the concentration of metal ions in the mixed solution is 50-75 mmol / L, preferably 50-60 mmol / L. Specifically, the concentration of metal ions in the mixed solution is 50 mmol / L, 55 mmol / L, 60 mmol / L, 65 mmol / L, 70 mmol / L or 75 mmol / L. A suitable metal ion concentration can increase the reaction rate while ensuring economic benefits.

[0051] According to an embodiment of the present disclosure, the ratio of metal ions to surfactants in the mixed solution is (2.5-3.75) mmol: (0.5-2) g, preferably (3.0-3.5) mmol: (1-2) g. Specifically, the ratio of metal ions to surfactants in the mixed solution can be 2.5 mmol: 0.5 g, 2.5 mmol: 1 g, 2.5 mmol: 1.5 g, 2.5 mmol: 2 g, 3 mmol: 0.5 g, 3 mmol: 1.0 g, 3 mmol: 1.5 g, 3 mmol: 2 g, 3.75 mmol: 0.5 g, 3.75 mmol: 1 g or 3.75 mmol: 1.5 g or 3.75 mmol: 2 g. A suitable ratio of metal ions to surfactants can improve the morphology and performance of the ozone activation catalyst while ensuring economic benefits.

[0052] According to an embodiment of the present disclosure, the concentration of the potassium ferrocyanide solution is 50-75 mmol / L, preferably 50-60 mmol / L. Specifically, the concentration of the potassium ferrocyanide solution can be 50 mmol / L, 55 mmol / L, 60 mmol / L, 65 mmol / L, 70 mmol / L or 75 mmol / L. A suitable potassium ferrocyanide solution can increase the reaction rate while ensuring economic benefits.

[0053] According to an embodiment of the present disclosure, slow addition means that the potassium ferrocyanide solution is not added all at once, but is added in batches or continuously within a predetermined time. Specifically, the potassium ferrocyanide solution can be added to the mixed solution at a certain speed.

[0054] According to the embodiments of the present disclosure, the slow addition time is 1 to 10 min, preferably 1 to 5 min. Specifically, the slow addition time can be 1 min, 2 min, 3 min, 5 min, 8 min or 10 min. The appropriate addition time can promote the potassium ferricyanide solution and the mixed solution to fully react, which can ensure the morphology of the ozone activated catalyst and the economic benefit.

[0055] According to an embodiment of the present disclosure, the reaction time is 4 to 6 hours. Specifically, the reaction time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0056] According to an embodiment of the present disclosure, the steps of adding and reacting are carried out under stirring conditions, and the stirring rate is 800-1200 rpm. Specifically, the stirring rate can be 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or 1200 rpm.

[0057] According to an embodiment of the present disclosure, the standing time is 15 to 20 hours. Specifically, the standing time can be 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours.

[0058] According to an embodiment of the present disclosure, the calcination temperature is 500-700°C, preferably 500-650°C, specifically, the calcination temperature can be 500°C, 550°C, 600°C, 650°C, 680°C or 700°C, preferably 600°C; the calcination time is 2-4 h, specifically, the calcination time can be 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0059] According to the embodiments of the present disclosure, a suitable calcination temperature is conducive to efficiently obtaining an ozone activation catalyst with excellent performance. If the calcination temperature is too low, the carbon material shell cannot form a complete carbon-wrapped structure; if the calcination temperature is too high, the carbon material shell is too dense, which is not conducive to exerting the high reactivity of the metal alloy.

[0060] According to an embodiment of the present disclosure, the heating rate of calcination is 3-8°C / min, preferably 4-6°C / min, specifically 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min, preferably 5°C / min.

[0061] According to an embodiment of the present disclosure, the preparation method of the ozone-activated catalyst further includes: acid washing, water washing and ethanol washing after cooling the calcined ozone-activated catalyst. Specifically, the acid washing can be heated to 90°C in a 1.0 mol / L H2SO4 solution for 4 hours to remove the metal remaining on the surface.

[0062] According to an embodiment of another aspect of the present disclosure, there is provided an application of the above ozone-activated catalyst or the ozone-activated catalyst prepared by the above preparation method in conjunction with ozone in sewage treatment.

[0063] The ozone activation catalyst provided by the embodiments of the present disclosure has high catalytic activity, good stability, and can be reused.

[0064] The following lists a number of specific embodiments to illustrate the technical solution of the present disclosure in detail. It should be noted that the specific embodiments below are only used for illustration and are not intended to limit the present disclosure.

[0065] Example 1

[0066] This embodiment provides an ozone activation catalyst, including a core, the core comprising a cobalt-iron alloy; and a shell formed on the outer surface of the core, the shell comprising a carbon material.

[0067] This embodiment also provides a method for preparing the above-mentioned ozone activation catalyst, comprising the following steps:

[0068] (1) Add 50 mL of deionized water and CoCl2•6H2O in a 200 mL beaker, where the Co ion concentration is 50 mmol / L. Then add 1.5 g of polyvinyl pyrrolidone (PVP) to the solution. W The concentration of 50000 was stirred and dissolved until the solution was clear, which was recorded as solution A.

[0069] (2) Add 50 mL of deionized water and 50 mmol / L K3[Fe(CN)6] to another beaker and stir until the solution becomes clear. This is called Solution B.

[0070] (3) Stir solution A at 800 rpm, slowly add solution B for 2 min, continue stirring at 800 rpm for 4 h, and then let stand for 20 h. Separate the precipitate by high-speed centrifugation and wash it with deionized water several times. Dry the washed solid in a vacuum oven at 60 °C for 24 h to obtain the precursor.

[0071] (4) After the precursor was ground, it was calcined in an argon-protected tube furnace at a heating rate of 5 °C / min to 600 °C and maintained for 4 h (Ar flow rate 50 mL / min). After cooling, the obtained sample was heated to 90 °C in a 1.0 mol / L H2SO4 solution for 4 h to remove the residual metal on the surface. Finally, it was washed three times with deionized water and ethanol to obtain an ozone-activated catalyst, which was recorded as FeCo (600)@C.

[0072] Example 2

[0073] This embodiment provides an ozone activation catalyst, including a core, the core comprising a nickel-iron alloy; and a shell layer formed on the outer surface of the core, the shell layer comprising a carbon material.

[0074] This embodiment also provides a method for preparing the above-mentioned ozone-activated catalyst, referring to Example 1, except that in step (1), CoCl2•6H2O is replaced by an equimolar amount of NiCl2•6H2O, and the prepared ozone-activated catalyst is recorded as FeNi (1.5 g pvp) @C.

[0075] Example 3

[0076] This embodiment provides an ozone activation catalyst, including a core, the core comprising a nickel-iron alloy; and a shell layer formed on the outer surface of the core, the shell layer comprising a carbon material.

[0077] This embodiment also provides a method for preparing the above-mentioned ozone-activated catalyst, referring to Example 1, except that the amount of pvp added in step (1) is 0.5 g, and the prepared ozone-activated catalyst is recorded as FeNi (0.5 g pvp)@C.

[0078] Example 4

[0079] This embodiment provides an ozone activation catalyst, including a core, the core comprising a cobalt-iron alloy; and a shell formed on the outer surface of the core, the shell comprising a carbon material.

[0080] This example also provides a method for preparing the above-mentioned ozone-activated catalyst, referring to Example 1, except that the calcination temperature in step (4) is 500°C, and the prepared ozone-activated catalyst is denoted as FeCo (500)@C.

[0081] Example 5

[0082] This embodiment provides an ozone activation catalyst, including a core, the core comprising a cobalt-iron alloy; and a shell formed on the outer surface of the core, the shell comprising a carbon material.

[0083] This example also provides a method for preparing the above-mentioned ozone-activated catalyst, referring to Example 1, except that the calcination temperature in step (4) is 700°C, and the prepared ozone-activated catalyst is denoted as FeCo (700)@C.

[0084] Example 6

[0085] This embodiment provides an ozone activation catalyst, including a core, the core comprising a nickel-iron alloy; and a shell layer formed on the outer surface of the core, the shell layer comprising a carbon material.

[0086] This embodiment also provides a method for preparing the above-mentioned ozone-activated catalyst, referring to Example 1, except that in step (1), CoCl2•6H2O is replaced by 60 mmol / L NiCl2•6H2O; in step (3), stirring is continued at a speed of 1000 rpm for 6 h, and then the mixture is allowed to stand for aging for 18 h.

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing an ozone-activated catalyst, referring to Example 1, except that in step (1), CoCl2•6H2O is replaced by an equimolar amount of MnCl2•6H2O, and the prepared ozone-activated catalyst is recorded as FeMn@C.

[0089] Comparative Example 2

[0090] This comparative example provides a method for preparing an ozone-activated catalyst, referring to Example 1, except that in step (1), CoCl2•6H2O is replaced by an equimolar amount of FeCl2•6H2O, and the prepared ozone-activated catalyst is denoted as Fe@C.

[0091] The FeCo(600)@C provided in Example 1, the FeCo(500)@C provided in Example 4, and the FeCo(700)@C provided in Example 5 were analyzed by transmission electron microscopy (TEM) and Raman spectroscopy. Figures 1 to 4 As shown. Among them, Figure 1 shows a transmission electron microscope image of FeCo (600)@C provided in Example 1; Figure 2 shows a transmission electron microscope image of FeCo (500)@C provided in Example 4; Figure 3 shows a transmission electron microscope image of FeCo (700)@C provided in Example 5; Figure 4 Raman images of ozone activated catalysts provided in Examples 1, 4 and 5 are shown. Figure 1 It can be seen that FeCo (600) @ C has a regular spherical structure. Since the contrast of the metal alloy is greater, the color in TEM is darker, while the contrast of carbon is smaller. The core (metal alloy) shell (carbon) structure of FeCo @ C can be clearly seen from the figure. The particle size is 20~50 nm, and the thickness of the shell is 2~8 nm. Figures 1 to 3Analysis shows that compared with FeCo (600)@C, FeCo (500)@C contains a large number of hollow carbon spheres without metal, indicating that under 500 °C, the material cannot form a complete carbon-wrapped structure. Therefore, during the pickling process, the internal metal will dissolve to form hollow spheres; while FeCo (700)@C has a thicker carbon layer and more layered structures. Combined with Raman spectroscopy ( Figure 4 ) It can be seen that compared with FeCo (500)@C and FeCo (600)@C, the G band and D band of the graphene structure in FeCo (700)@C have obvious blue shifts, which also indicates that it has a thicker carbon coating. Figures 1 to 4 It can be seen that the carbon material shells of FeCo (500)@C, FeCo (600)@C and FeCo (700)@C include graphene structures, and the precursors will form more flaky graphene structures at 700 °C.

[0092] The FeMn@C provided in Comparative Example 1 was characterized by TEM. Figure 5 As shown. Figure 5 It can be seen that FeMn@C exhibits an irregular morphological distribution and no obvious core-shell structure appears.

[0093] The FeCo (600)@C provided in Example 1 and the FeNi@C (1.5 g pvp) provided in Example 2 were characterized by X-ray diffraction (XRD). Figure 6 .Depend on Figure 6 Analysis shows that the metals in FeCo (600)@C mainly exist in the form of simple substances, in addition to a small amount of C. In FeNi@C (1.5 g pvp), the metals exist in the form of simple substances as well as metal carbides, and the C content is also higher.

[0094] The FeNi@C (0.5 g pvp) provided in Example 3 and the FeNi@C (1.5 g pvp) provided in Example 2 were characterized by XRD. The results are as follows: Figure 7 .Depend on Figure 7 Analysis shows that the addition of polyvinyl pyrrolidone changes the content of C component and metal carbide in FeNi@C, and the proportion of carbon material in FeNi@C (0.5 g pvp) catalyst is higher.

[0095] The FeCo(600)@C provided in Example 1 and the Fe@C provided in Comparative Example 2 were compared by XRD. Figure 8 As shown. Figure 8 Analysis shows that when only metal Fe is added, the metal cannot be reduced at high temperature, and Fe exists in the form of FeC3, and there is no metal single substance structure.

[0096] Application Example 1

[0097] (1) Using pure oxygen as the gas source, generate O3 through an ozone generator. Use an ozone concentration detector to measure the O3 concentration in real time and control the ozone concentration to 30 mg / L. Use a gas flow meter to maintain the ozone flow rate at 100 mL / min.

[0098] (2) The generated O3 was introduced into the mixed aqueous solution of the catalyst and the pollutant, and the reaction was carried out in a 150 mL three-necked flask at a temperature of 25±2°C. Since the material is magnetic, the reaction system was mixed by mechanical stirring at a speed of 500 rpm.

[0099] (3) Oxalic acid (OA) was selected as the pollutant in step 2: 100 mL of 50 mg / L oxalic acid solution was prepared and added to a three-necked flask. 0.02 g of FeCo (600)@C provided in Example 1, FeNi@C (1.5 g pvp) provided in Example 2, FeMn@C provided in Comparative Example 1, and no catalyst were added to the solution, and O3 was passed into the suspension, and samples were taken at fixed time intervals. After sodium sulfite was added to terminate the reaction, the suspension was filtered with a 0.22 μm filter membrane, and the concentration of the pollutant was tested using high performance liquid chromatography (HPLC).

[0100] The degradation curve obtained in the test of Application Example 1 is as follows Fig. 9 As shown, from Fig. 9 It can be seen that ozone itself has almost no degradation effect on oxalic acid. After adding FeMn@C, oxalic acid is almost not degraded, while the addition of FeCo (600)@C and FeNi@C (1.5 gpvp) significantly improves the degradation efficiency of oxalic acid. Among them, FeCo (600)@C has the best catalytic ozone oxidation performance, which can achieve complete oxidation of oxalic acid in 25 min.

[0101] Application Example 2

[0102] The steps of this application example refer to those of application example 1, except that step (3) is:

[0103] (3) Oxalic acid (OA) was selected as the pollutant in step 2: 100 mL of 50 mg / L oxalic acid solution was prepared and added to a three-necked flask. After adding 0.02 g of FeCo (600)@C provided in Example 1, FeCo (500)@C provided in Example 4, and FeCo (700)@C provided in Example 5, respectively, O3 was introduced into the suspension, and samples were taken at fixed intervals. After sodium sulfite was added to terminate the reaction, the suspension was filtered with a 0.22 μm filter membrane, and the concentration of the pollutant was tested using a high performance liquid chromatograph (HPLC).

[0104] The degradation curve obtained in the test of Application Example 2 is as follows: Fig.10 As shown, from Fig.10 It can be seen that the ozone-activated catalysts synthesized at different temperatures have different catalytic ozone oxidation performance. Among them, FeCo (600)@C has the best pollutant degradation ability. The degradation ability of FeCo (700)@C for pollutants is slightly worse. This may be because the carbon material shell in FeCo (700)@C is too dense, which is not conducive to the high reactivity of the metal alloy; and a complete carbon material shell cannot be formed on the surface of FeCo (500)@C. It can be seen that the appropriate calcination temperature is conducive to the efficient acquisition of ozone-activated catalysts with excellent performance, and the formation of a suitable carbon material shell is the key to affecting the ozone catalytic oxidation performance of the ozone-activated catalyst.

[0105] Application Example 3

[0106] The steps of this application example refer to those of application example 1, except that step (3) is:

[0107] (3) Phenol (PhOH) was selected as the pollutant in step 2: 100 mL of a 50 mg / L phenol solution was prepared and added to a three-necked flask. After adding 0.02 g of FeCo (600)@C provided in Example 1 and FeCo(500)@C provided in Example 4 to the solution, O3 was introduced into the suspension, samples were taken at fixed intervals, ascorbic acid was added to terminate the reaction, and then the concentration of the pollutant was tested after filtering with a 0.22 μm filter membrane.

[0108] The test results in Application Example 3 are as follows: Fig.11 As shown in the figure, for pollutants such as phenol, ozone itself can also directly oxidize them, and after adding FeCo (600)@C and FeCo (500)@C, the degradation efficiency of phenol is significantly improved. Fig.11 It can be seen that after adding the catalyst, the pollutants can be completely degraded in 15 minutes. The efficiency of the two catalysts in catalyzing ozone degradation of phenol is slightly different.

[0109] Application Example 4

[0110] The steps of this application example refer to those of application example 1, except that step (3) is:

[0111] (3) Oxalic acid was selected as the pollutant in step 2: 100 mL of 50 mg / L oxalic acid solution was prepared and added to a three-necked flask. After adding 0.02 g of the catalyst FeCo (600)@C provided in Example 1 to the solution, O3 was introduced into the suspension, samples were taken at fixed time intervals, sodium sulfite was added to terminate the reaction, and then the concentration of the pollutant was tested after filtering with a 0.22 μm filter membrane.

[0112] This application example also includes step (4):

[0113] (4) Cyclic stability experiment: The catalyst after the reaction in step (3) was collected, washed with deionized water three times, separated by solid-liquid centrifugation, and vacuum dried at 40°C to obtain the catalyst after the reaction.

[0114] Then, the operations of steps (3) and (4) were repeated to obtain the degradation curve of FeCo (600)@C after 5 cycles, as shown in FIG. Fig.12 shown.

[0115] from Fig.12 It can be seen that the FeCo@C / O3 system can complete the oxidation degradation of oxalic acid in half an hour, and after being recycled for 5 times, it still maintains good catalytic activity. This result shows that the ozone activated catalyst provided by the present disclosure has good stability in the ozone catalytic oxidation water treatment process.

[0116] The above is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. Any modification, equivalent replacement, improvement, etc. made to the technical method by any technician familiar with the art within the spirit and principle of the present disclosure is still included in the protection scope of the technical solution of the present disclosure.

Claims

1. An ozone activation catalyst, characterized in that The ozone activation catalyst comprises: a core, the core comprising a cobalt-iron alloy or a nickel-iron alloy; A shell layer is formed on the outer surface of the inner core, and the shell layer includes a carbon material.

2. The ozone activation catalyst according to claim 1, characterized in that The inner core includes a cobalt-iron alloy.

3. The ozone activation catalyst according to claim 1 or 2, characterized in that: The size of the ozone activation catalyst is 20-50 nm; The thickness of the shell layer is 2-8 nm.

4. The ozone activation catalyst according to claim 1 or 2, characterized in that: The molar ratio of cobalt to iron in the cobalt-iron alloy is (2-3): (2-3); The molar ratio of nickel to iron in nickel-iron alloy is (2~3):(2~3).

5. A method for preparing an ozone activated catalyst, characterized in that: The following steps are involved: Slowly adding a potassium ferrocyanide solution into a mixed solution containing metal ions and a surfactant to react, and then sequentially standing and separating to obtain a precursor; calcining the precursor in a protective atmosphere to obtain the ozone activated catalyst; Wherein, the metal ions include cobalt ions or nickel ions.

6. The preparation method according to claim 5, characterized in that: The calcination temperature is 500-700°C and the time is 2-4 hours; The heating rate of the calcination is 3-8 °C / min.

7. The preparation method according to claim 5 or 6, characterized in that: The concentration of metal ions in the mixed solution is 50-75 mmol / L; The ratio of metal ions to surfactants in the mixed solution is (2.5-3.75) mmol: (0.5-2) g; The concentration of the potassium ferrocyanide solution is 50-75 mmol / L.

8. The preparation method according to claim 5 or 6, characterized in that: The surfactant is a high molecular surfactant with a weight average molecular weight of 30,000 to 50,000, preferably one or more of polyvinyl pyrrolidone, polyacrylic acid, and carboxymethyl cellulose.

9. The preparation method according to claim 5 or 6, characterized in that: The slow addition time is 1 to 10 minutes; The reaction time is 4 to 6 h; The standing time is 15 to 20 h.

10. Use of the ozone activated catalyst according to any one of claims 1 to 4 or the ozone activated catalyst prepared by the preparation method according to any one of claims 5 to 9 in combination with ozone in sewage treatment.

Citation Information

Patent Citations

  • Iron-cobalt doped ozone activation catalyst Fe-CoOx and preparation method thereof

    CN115090287A